Work‑Life Balance, Lingkungan Kerja, dan Kinerja Pegawai dalam Kerangka Hukum Kesehatan - Arini Asriyani; Arfandy Dinsar; Muhamamd Darwis (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2026)
This study aims to analyze the effect of work‑life balance and work environment on employee performance and to examine its implications for compliance with legal norms and professional ethics of health workers at Regional Hospital dr. Hasri Ainun Habibie in Parepare City. A quantitative approach was employed using a saturated sampling technique involving 74 civil servant employees, with data collected through questionnaires that had been tested for validity and reliability, and analyzed using multiple linear regression, t‑tests, F‑tests, and the coefficient of determination. These empirical analyses were complemented by a normative review of relevant legislation and professional codes of ethics. The results indicate that work‑life balance and work environment have a significant effect, both partially and simultaneously, on employee performance, and normatively suggest the need to strengthen hospital human resource policies to ensure balanced work–life conditions and a decent work environment as part of the legal and ethical obligations of public hospitals.